2016
DOI: 10.1111/wrr.12463
|View full text |Cite
|
Sign up to set email alerts
|

Combination of ciclopirox olamine and sphingosine‐1‐phosphate as granulation enhancer in diabetic wounds

Abstract: Granulation tissue formation requires a robust angiogenic response. As granulation tissue develops, collagen fibers are deposited and compacted. Forces generated in the wake of this process drive wound contraction to reduce the wound area. In diabetics, both angiogenesis and wound contraction are diminished leading to impaired wound healing. To emulate this pathology and to address it pharmacologically, we developed a wound healing model in the diabetic Zucker fatty rat and tested a topical proangiogenic strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Alternatively, the PVA implants may be preloaded or continuously injected with a control vehicle or an experimental treatment solution to evaluate its impact on the migratory properties of different wound-bed cell populations, rate of granulation tissue (GT) formation and its health (thickness, vascularity), lymphangiogensis as well as deposition of extracellular matrix (ECM) and collagen bers (72)(73)(74)(75).…”
Section: Overview Of Befaf Modelmentioning
confidence: 99%
“…Alternatively, the PVA implants may be preloaded or continuously injected with a control vehicle or an experimental treatment solution to evaluate its impact on the migratory properties of different wound-bed cell populations, rate of granulation tissue (GT) formation and its health (thickness, vascularity), lymphangiogensis as well as deposition of extracellular matrix (ECM) and collagen bers (72)(73)(74)(75).…”
Section: Overview Of Befaf Modelmentioning
confidence: 99%
“…When exposed to S1P in vitro, these cells preferentially adopt anti‐inflammatory phenotypes and display a reduced secretion of proinflammatory cytokines if stimulated . Lim et al used S1P in combination with the antifungal agent ciclopirox olamine, which also displays proangiogenic activity . The group found that injection of the two agents into a polyvinyl alcohol sponge implanted in diabetic fatty rats supported endothelial migration and the formation of functional vessels.…”
Section: Advanced Tissue Engineering Approaches To Regenerate Skinmentioning
confidence: 99%
“…However, in context with mesenchymal cells and unwounded or wounded tissue it became clear that angiogenic HIF1-α effects of PH inhibitors, even as so-called dirty tool, prevail. Shortly after the publication by Clement, and the mesenchymal endothelial crosstalk leading to angiogenesis was later demonstrated in greater detail in microfluidics systems [210,212] and diabetic wounds in experimental animal models [213,214]. The change viewpoints on PH inhibitors over time in the literature over time shows the importance of considering and implementing cellular cross-talk in angiogenic assays in vitro, as ECs are not the greatest producers of angiogenic factors, but rather the recipients of signals through them.…”
Section: Hypoxia Mimicking Strategiesmentioning
confidence: 99%